Editorial JSE 24:4 - Braude, Stephen (Journal of Scientific Exploration, 2010)
ISSUE DESCRIPTION The The Journal of Scientific Exploration is devoted to the open-minded examination of scientific anomalies and other topics on the scientific frontier. Its articles and reviews, written by authorities in their respective fields, cover both data and theory in areas of science that are too often ignored or treated superficially by other scientific publications. This issue of the journal features papers on a variety of subjects. The lead article presents the results of an innovative ball-selection test for ESP, including a successful replication under tighter and presumably more repressive conditions under skeptical supervision at the University of London. The next paper presents a double-blind study of apparent short-term precognition in Bengalese finches. The test tracked whether the birds displayed alarm behavior prior to the random display of a crawling snake video. The third paper discusses an original approach to the study of ostensible macroscopic psychokinetic phenomena produced in a mediumistic sitter-group setting. The participants tried to generate a pseudo-spirit similar to that in the famous Philip experiments, and the researchers deployed various strategies for detecting and measuring physical correlates of the phenomena observed during the sessions. The fourth paper reports an attempt to use random number generators to detect field consciousness while people watched a film in a movie theater. In the fifth paper, researchers report a study that used advanced signal-processing techniques and instantaneous EEG phase coupling to examine interpersonal connectivity between healer and subject. The final paper presents two studies designed to illustrate how laboratory ESP effects might be used to predict real-world, practical events--in this case, the behavior of sets of financial indices. This issue of the JSE is then filled out, as usual, with a large selection of substantive book reviews.